If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 5) = 6 + -3(n + -7) Reorder the terms: 3(5 + n) = 6 + -3(n + -7) (5 * 3 + n * 3) = 6 + -3(n + -7) (15 + 3n) = 6 + -3(n + -7) Reorder the terms: 15 + 3n = 6 + -3(-7 + n) 15 + 3n = 6 + (-7 * -3 + n * -3) 15 + 3n = 6 + (21 + -3n) Combine like terms: 6 + 21 = 27 15 + 3n = 27 + -3n Solving 15 + 3n = 27 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 15 + 3n + 3n = 27 + -3n + 3n Combine like terms: 3n + 3n = 6n 15 + 6n = 27 + -3n + 3n Combine like terms: -3n + 3n = 0 15 + 6n = 27 + 0 15 + 6n = 27 Add '-15' to each side of the equation. 15 + -15 + 6n = 27 + -15 Combine like terms: 15 + -15 = 0 0 + 6n = 27 + -15 6n = 27 + -15 Combine like terms: 27 + -15 = 12 6n = 12 Divide each side by '6'. n = 2 Simplifying n = 2
| -3x+5y-7=0 | | 8(1.5+.5y)-4y=12 | | 5-2(x+5)=40 | | 4x(126)= | | 20-5s=8 | | x^2(x-3)(x^2-9)(x^2+4)=0 | | W=Fa+FB | | 6x^2(36)= | | x^2+18x+y^2=-17 | | (4x+3)-5=5(x+4) | | x*12+-42+85=246 | | 74=10+4x | | 5y-7+y+27=5y+20-3y | | 7(0)-2(6)=12 | | x^2+y^2+18x+17=0 | | x(x)=16316 | | 190=-8+9x | | 8x-14=-16 | | 7(5x+8)=-x+4 | | 0.10(y-9)+0.12y=0.18y-0.07(10) | | 7(5x+8)=-x+4 | | 8(2x+1)=7x+7 | | 4-9=6+x | | 4-9=6+x | | 4-9=6+x | | x-47=28 | | 4x^3(6)= | | 4=x/2+8 | | 32-4(9-2)=4(T-1) | | -81=-4x+3 | | X+1(4x-2)=2x-1(3x-1) | | 20-3z=7z+8 |